Regional Specialization via Differences in Transport Costs - Hajime Takatsuka; Dao-Zhi Zeng (European Regional Science Association (ERSA), 2005)
This paper examines a new economic geography model with multiple (three) industries and urban costs. The industries are asymmetric in their transport costs. The following results were obtained. First, if transport costs sufficiently decrease whereas commuting costs are constant, we have three stable location patterns; full dispersion, partial regional specialization, and complete regional specialization. Second, if commuting costs sufficiently decrease (resp. increase) whereas transport costs are constant, we have full agglomeration (resp. full dispersion). The cases with medium value of transport and commuting costs and with multiple (three) regions are analyzed by use of numerical simulation.
Keywords: 330